Potensi Antibakteri Kombinan Zingiber officinale var. Rubrum dengan Cinnamomum burmannii terhadap Staphylococcus aureus - Ruth Mayana Rumanti; Suprianto; Jakub Tarigan; Arinri Misnangin Sritala Ramadani (Jurnal Indah Sains dan Klinis, 2021)
Red Ginger (Zingiber officinalevar. Rubrum) and Cinnamon (Cinnamomum burmannii) contain alkaloids, flavonoids, saponins, tannins, triterpenoids and essential oils. which is antibacterial that causes pharyngitis by Staphylococcus aureus. This study aims to determine the antibacterial potency of the combination of Red Ginger (Zingiberofficinalevar. Rubrum) and Cinnamon (Cinnamomum burmannii) extract against Staphylococcus aureus. Experimental research includes the extraction of the compound components in red ginger and cinnamon by maceration with 70% ethanol. Inhibition was tested bydiffusion method. Combination of concentration of Red Ginger and Cinnamon extracts of 5%:40%; 10%:30%; 20%:20%; 30%:10% and 40%:5%. The combination of red ginger and cinnamon extract has antibacterial activity against pharyngitis-causing bacteria, namely Staphylococcus aureuswith a strong response at a concentration of 5%:40%